Facile synthesis of MnO2/g-C3N4 for photocatalytic reduction of methylene blue dye under visible light - Abdullah, Muhammad; Alahmari, Saeed D.; Alharbi, F. F.; Ejaz, Syeda Rabia; Waheed, Muhammad Suleman; Aman, Salma; Al-Sehemi, Abdullah G.; Henaish, A. M. A.; Ahmad, Zubair; Farid, Hafiz Muhammad Tahir (Journal of materials science. Materials in electronics, 2024)
Water pollution has recently come to the forefront of people’s minds because of the widespread textile dye contamination. It suffers from a wide variety of harmful chemicals in the textile, cosmetics, food, and paint industries and these are removed by photocatalysis. Photocatalytic degradation is considered an efficient approach for the elimination of toxic pollutants from industrial effluents. In this work, MnO 2 /g-C 3 N 4 nanocomposite was developed hydrothermally for photocatalytic mineralization of methylene blue (MB) dye. The surface study revealed that MnO 2 /g-C 3 N 4 shows a greater surface area (97 m 2 g −1 ) attributed to the g-CN nanosheet. The photocatalytic efficiency of MnO 2 , g-C 3 N 4 & MnO 2 /g-C 3 N 4 materials was additionally ascertained via the degradation of MB, which was considered to be a model dye. The MnO 2 , g-C 3 N 4 & MnO 2 /g-C 3 N 4 display the photocatalytic efficiency of 72.34, 85.81, and 94.32%, respectively. According to the TOC study, the MnO2/g-C3N4 nanocomposite showed a degradation rate of 71.23% over a period of 150 min. The scavenger analysis revealed that charge species (hydroxyl, hole and superoxide anion) play a substantial part in the photodegradation of dyes. The results show that the fabricated nanocomposite shows maximum photocatalytic efficacy compared to pristine material due to the appropriate bandgap along with unique structural features. The developed catalyst not only has the potential to degrade the dye and it can also work in other energy storage applications.